Effects of hydroxy safflower Yellow-A on tumor capillary angiogenesis in transplanted human gastric adenocarcinoma BGC-823 tumors in nude mice - 奚胜艳 张前 刘朝阳 解华 岳利峰 高学敏 (Journal of Traditional Chinese Medicine, 2012)
OBJECTIVE：To study the effects of hydroxy safflower yellow A（HSYA） on tumor capillary angiogenesis in transplanted human gastric adenocarcinoma BGC-823 tumors in nude mice.METHODS：BGC-823 cells were injected subcutaneously into the right anterior armpit of nude mice to establish an animal model of transplanted tumors.After 24 h,18 nude mice injected with tumor cells were randomized into model,control,and HSYA 0.028 g/L groups,with six mice in each group.Transplanted tumors were excised on day 20.Tumor inhibition ratios were calculated for the transplanted tumors.Pathological changes and capillary angiogenesis in the tumors were observed by light microscopy.RESULTS：Tumors in the model group grew more quickly than those in the control and HSYA groups,with inhibition ratios of 48% and 30%,respectively.The microvessel count in the HSYA group was lower than in the model group（P〈0.01）,and microvessel density was also lower in the HSYA group（P〈0.05）.Pathological changes were more obvious in tumors in the model group compared to the HSYA group.CONCLUSION：HSYA inhibits the growth of transplanted BGC-823 tumors,and its effects on tumor capillary angiogenesis may represent one of the mechanisms responsible for this antineoplastic effect.